Rural Education in Paraná: an analysis from Guarapuava (1930-1960) - Denise Sikora; Angela Maria Hidalgo; Carlos Herold Junior (Universidade Federal do Rio Grande do Sul, 2015)
The aim of this paper is to analyze different stances on the importance of rural education in the city of Guarapuava, from 1930 to 1960. Having as empirical basis newspapers distributed in the city, we also use other documents to think the matter under a perspective that crosses the national, the state and the municipal level. As a result of this analytical path, we can see that rural education in Guarapuava expresses its importance alternating the advocacy of the value of education and denunciations regarding problems to realize this educational modality.